Application of Artificial Neural Network for Prediction of Marine Diesel Engine Performance - C. W., Mohd Noor; R., Mamat; G., Najafi; W. B., Wan Nik; M., Fadhil (IOP Publishing, 2015)
This study deals with an artificial neural network (AIIN) modelling of a marine diesel engine to predict the brake power, output torque, brake specific fuel consumption, brake &ermal effrciency and volumetric efficiency. The input data for network training was gathered from engine laboratory testing running at various engine speed. The prediction model was developed based on standard back-propagation Levenberg-Marquardt training algorithm. The performance of the model was validated by comparing the prediction data sets with the measured experiment data. Results showed that the ANN model provided good agreement with the experimental data with high accuracy.